On the continuous (R)evolution of antibody-based and CAR T cell therapies in multiple myeloma: an early 2022 glance into the future. (13th August 2022) - Sunder-Plassmann, Vincent; Aksoy, Osman; Lind, Judith; Pecherstorfer, Martin; Vallet, Sonia; Podar, Klaus
ABSTRACT: Introduction: The pace at which the identification of novel therapeutic targets has led to the approval of multiple myeloma (MM) agents during the last two decades is nothing more than spectacular. Nevertheless, MM remains an incurable disease. Therefore, there is an urgent need for additional, innovative therapeutics. Immune dysfunction and the tumor-permissive immune bone marrow microenvironment represent hallmarks of MM pathophysiology. Naked monoclonal antibodies directed against SLAMF7 and CD38 already constitute backbones of today's MM therapy. Novel immunotherapeutic modalities including antibody-drug-conjugates (ADC), bispecific antibodies (BsAb), and chimeric-antigen-receptor T cells are on the way to once more revolutionize future MM therapy. Areas covered: The present review article summarizes the most recent results on MM immunotherapies presented at the 2021 Annual Meeting of the American Society of Hematology; and throws a glance on ongoing preclinical and clinical efforts aiming at further increasing their efficacy, while reducing their toxicity. Expert opinion: With the approvals of the first-in-class BCMA-targeting ADC (belantamab mafodotin) and two BCMA-targeting CAR T cell products (Ide-cel, Cilta-cel); and the approval of the first-in-class BCMAxCD3 BsAb immediately pending, the era of modern next-generation immunotherapies in MM is continuously evolving. Long-term disease-free survival and potential cure of MM are finally within reach.